Analysis of the contents of consultations requested by the emergency department - Boğan, Mustafa; Sultanoğlu, Hasan; Demir, Mehmet Cihat; Karadağ, Mehmet; Altınsoy, Hasan Baki (IMC Journal of Medical Science, 2021)
Background and objectives: Every year several thousand patients attend the hospital emergency department (ED). The aim of the present study was to evaluate the content of the consultations requested from the emergency department. Methods: The patients who had presented to the adult emergency department between January 1, 2020 and January 31, 2020, and who had undergone consultation by at least one clinic were included in the study. Age, gender, the number of consultation required at the same admission, the clinic from which the consultation sought, time required to respond to the request and the outcomes of the consultations were analyzed. Results: The total number of emergency department presentations was 8930 patients and at least one consultation had been requested for 6.64% (n = 593) patients. The mean duration of answering the consultation was 85.76 ± 90.33 minutes. Consultations were requested from the cardiology most frequently (n = 188, 19%), followed by the pulmonology department (n = 181, 18.3%). Discharge was recommended with prescription in 235 (39.6%) consultations. Internal medicine was the clinic, which recommended treatment at the emergency room most frequently (n = 45, 22.4%) and the most commonly recommended treatment was erythrocyte suspension replacement (n = 7). The clinic that demanded additional tests most commonly was determined to be the pulmonology department (n = 41, 22.9%) and arterial blood gases analysis was the most commonly demanded test (n = 16). Conclusion: In our study, the rate of consultations requested was seen to be lower and the rate of cases that required hospitalization was seen to be higher. The duration of answering consultations was found to be longer than desired and institutional protocols should be developed for shortening this duration. Ibrahim Med. Coll. J. 2021; 15(1): 9-15